BE THE CREATIVE INDIVIDU IN NEW NORMAL ERA: TRAINING OF PHOTOGRAPH FOR MILLENIAL GENERATION - MEI CHANDRA (Universitas Nahdlatul Ulama Lampung, 2021)
The existence of Covid-19 given impact directly to community life, did not only about health, but also for economy. Limitations for government activity increase these impact. Many people have been enemployment, then community, decrease of people purchasing power caused unstable economic cycle. People were being instructed stay at home for decrease contagion and transmittal virus Covid-19. This matter caused people be unproductive because they should be “kaum rebahan” that reffer to just at home in pandemic Covid-19 period. Based on problems mentioned above, this dedication community of Program Studi Komunikasi and Penyiaran Islam IAIN Surakarta took “Penguatan Dampak Covid-19” as theme. This dedication community did in form of training of photograph to millenial generation in order they`ll stay productive in Covid-19 pandemic period. This activity did “Training of photograph for millenial generation” purposed to karang taruna (youth organization)Pucangan, Kartasura, Sukoharjo, Central Java, did on June 20th 2020 located in Pucangan Office. Purpose of this activity for give information and basic knowledge about photograph to karang taruna (youth organization) for used as photographer and increase photo quality that used for online shop. Method used in this event as presentation and discussion and practice. Material presentation about basics of photograph contnoued with discussion and finished with capture photo or picture practice. The result of this event, participants instructed to practice photo shoot with approach and basic knowledge about photograph to create good quality of images or photos. Good photos would give appearance as the photograph technique used by participants. This event wished to increase participants skill in produce sensitivity and sharpness of photos or images angle to create good photos to be uploaded in online shop to make consumers interest with only slook at the good photos or images. Besides, increase of the participants skill in photograph, could be a good and reliable photographer. It shoukd be a solution of millenial generation skill increase in the pandemi period to be productive and increase level of life people as generally.